The Influence of the Marketing Mix on Purchase Decisions Mediated by Buyer Satisfaction (Case Study of PT Wijaya Karya Beton, Tbk – Palembang Sales Area) - Riono, Riono; Helmi, Sulaiman (Program Pascasarjana STIE Amkop Makassar, 2023)
The importance of this research lies in the in-depth understanding of how marketing mix factors affect consumer purchasing decisions through the intermediary of buyer satisfaction. The purpose of this study was to analyze the relationship between product, price, place, promotion, buyer satisfaction, and purchase decisions, as well as examine the mediating role of buyer satisfaction in the relationship between marketing mix and purchasing decisions. This research method involves collecting data through a survey of respondents who are consumers of PT Wijaya Karya Beton, Tbk in the sales area of Palembang. The findings indicate that the marketing mix has a significant influence on purchasing decisions, with buyer satisfaction mediating the relationship between these variables. In conclusion, this study confirms the importance of the marketing mix in shaping purchasing decisions, as well as explains the mediating role played by buyer satisfaction in this relationship. These findings provide strategic implications for companies in designing more effective marketing strategies, taking into account the critical role of buyer satisfaction as an intermediary between marketing mix and purchasing decisions